The Elizabeth Gaskell collection [videorecording (DVD)]. - Davis, Carl, 1936-; Keane, John (John E.) (BBC Video : BBC Worldwide Ltd. : 2 Entertain : Distributed by BBC Worldwide Americas ; Distributed by Warner Home Video, 2008)
Cranford: For spinsters Deborah Jenkyns, the arbiter of correctness in Cranford, and Matty, her demurring sister, the town is a hub of intrigue. A handsome new doctor, Frank Harrison, has arrived from London, a retired Army captain and his daughters have moved into a house opposite the sisters, and the preparations for Lady Ludlow's garden party are under way. Everyone -- from charming rogue Dr. Marshland to mean Mrs. Jamieson and her lap dog -- talks, and is talked about, behind closed doors. The town also has its secrets, which it slowly reveals.